Análise da modulação autonômica cardíaca no pré e pósoperatório de cirurgia bariátrica e os efeitos de um programa de treinamento físico aeróbio em mulheres obesas mórbidas - Castello, Viviane (Universidade Federal de São Carlos, 2011)
Bariatric surgery has proven to be a helpful technique in the clinical treatment of obesity. In particular, gastric bypass surgery (CBG) has shown favorable results in terms of length of weight loss but also in long-term maintenance. However, it remains unclear whether a short period of surgery can improve the changes in cardiac autonomic nervous system that obese individuals have and if a program of aerobic exercise after CBG may contribute to the improvement of those changes. In this context, we proposed the development of two studies that could contribute with new information. The first study, entitled "Impact of aerobic exercise training on heart rate variability and functional capacity in obese women after gastric bypass surgery" aimed to evaluate whether a program of physical training with aerobic exercise for 12-week is capable of modifying the heart rate variability (HRV) and functional capacity of severely obese women 4 months after GBS (4GBS). Twenty-one women were randomized into a training group (TG) (submitted to an aerobic exercise program of 36 sessions) or control group (CG) and tested on two occasions: one week before the GBS (BGBS) and 4GBS through the variables anthropometric, body composition, record of heart rate (HR) and RR interval (R-Ri), and 6-min walk test (6MWT). The main findings were that only the TG showed a significant increase in HRV indices and the walking distance after 12-week of aerobic physical training. In conclusion, 12-week of aerobic physical training improves cardiac autonomic modulation and functional capacity 4GBS. The second study, entitled "Variability and heart rate kinetics during 6-min walk test in morbidly obese women - effects of an aerobic exercise training after gastric bypass surgery" aimed to evaluate whether morbidly obese women have altered kinetic HR and HRV during the 6MWD test, and determine whether 12-week of aerobic physical training after GBS can modify these indexes. Nineteen morbidly obese women were randomized to TG (submitted to the same physical training program that the previous study) or group without training (GST) and 12 eutrophic woman were evaluated in the CG. The women were evaluated in two occasions: BGBS and 4GBS through anthropometric variables, pulmonary function and recording of HR and R-Ri during the 6MWT. The main findings were that: (1) obese women showed alterations the index rMSSD of HRV and in the HR kinetics during the 6MWT, and (2) only the TG showed significant improvement of the HR kinetics during the 6MWT after physical training. In conclusion, morbidly obese women have a slow response of the HR kinetics and cardiac autonomic modulation during the 6MWT, and 12-week of aerobic physical training after GBS is able to accelerate these responses.
Keywords: Obesidade; Cirurgia bariátrica; Sistema nervoso autônomo; Obesidade mórbida; Aptidão física; Treinamento físico; Índice de massa corpórea; Bariatric surgery; Autonomic nervous system; Morbid obesity; Body mass index; Physical fitness; Physical training; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL